Reinvestigation Thermoelectric Properties of CuAlO2 - Chesta Ruttanapun; Wattana Kosalwat; Chalermpol Rudradawong; Phumin Jindajitawat; Prathan Buranasiri; Daengdesh Naenkieng; Narongchai Boonyopakorn; Adul Harnwunggmoung; Warawoot Thowladda; Worakarn Neeyakorn; Chanchana Thanachayanont; Anek Charoenphakdee; et al. (My University, 2014)
Bulk CuAlO2 delafossite has been synthesized by solid state reaction to reinvestigate the thermoelectric properties. The electrical conductivity, Seebeck coefficient and thermal conductivity were measured in a high temperature range of 300 to 960 K. The result of positive sign of Seebeck coefficient confirms p-type nature of CuAlO2 compund. The results of bulk sample for Seebeck coefficient, the electrical conductivity and thermal conductivity are range of 900 to 300 μV/K, of 0.01 to 2 S/cm, and of 3.5 W/mK to 1.5 W/mK. The maximum ZT value of bulk sample is 0.017 at a 960 K. These results can be concluded that the bulk CuAlO2 by solid state state displays thermoelelctric material.
Keywords: Delafossite; Atmospheric temperature range; Copper-based nanomaterials and applications